Enchanted Backburner: Channeling Taylor Swift and Niki on Cegil Identity - Tri Satya, Theresia Benedikta Laksya (Pengkajian Amerika, Universitas Gadjah Mada, 2024)
This study chooses a transnational perspective to understand the practice of American culture in Indonesia. As this study discussed identity formed in social media and involved popular music singers, the theories applied in this study are the theories of identity, youth culture, new media, and popular music from the popular culture approach. In examining this study, the content analysis method was applied. After reviewing primary and secondary sources and find suppported theories for the data, it is find that the cegil identity is channeled through Taylor Swift and NIKI’s musicality due to the interconnection of youth culture and new media in treating popular music. The star and stardom of Swift and NIKI influence people's perspectives on their songs. The cegil community likes their lyricism in descriptive, imaginative, and poetic songs. Global access and media allow Spotify and X as the mediums to communicate and participate for cegil to express their feelings. They were also the place where the cegil term was coined. The last factor is a youth culture that treats music as the soundtrack of life and hence sees songs as a medium to express themselves.